2014
DOI: 10.1002/pssa.201431652
|View full text |Cite
|
Sign up to set email alerts
|

Interface trap states in Al2O3/AlGaN/GaN structure induced by inductively coupled plasma etching of AlGaN surfaces

Abstract: We have investigated the effects of the inductively coupled plasma (ICP) etching of AlGaN surface on the resulting interface properties of the Al 2 O 3 /AlGaN/GaN structures. The experimentally measured capacitancevoltage (C-V) characteristics were compared with those calculated taking into account the interface states density at the Al 2 O 3 /AlGaN interface. As a complementary method, photoassisted C-V method utilizing photons with energies less than the bandgap of GaN was also used to probe the interface st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 24 publications
1
13
0
Order By: Relevance
“…16,24,29 However as shown in Fig. 9, the values of capture cross section remained similar among these samples.…”
Section: Discussionmentioning
confidence: 58%
See 1 more Smart Citation
“…16,24,29 However as shown in Fig. 9, the values of capture cross section remained similar among these samples.…”
Section: Discussionmentioning
confidence: 58%
“…2 sample exhibited the higher interface state density probably due to interface disorder. 16,24,29 The ᭝V th in C-V characteristics was measured in the following manner. The measurement steps and the corresponding band diagrams are schematically shown in Figs.…”
Section: Methodsmentioning
confidence: 99%
“…1, we present a scheme of the studied MISH structures, i.e. : The investigated heterostructures were passivated using the two-step process: [24][25][26][27][28] (1) covered by a SiN (10 nm) protection film deposited by electron cyclotron resonance chemical vapor deposition (ECR CVD) to avoid damages of semiconductor surfaces during ohmic contact annealing and (2) after removal of the SiN film, covered with an Al 2 O 3 layer (20 nm) deposited by atomic layer deposition (ALD)…”
Section: Sample Structure and Fabrication Processmentioning
confidence: 99%
“…Yatabe et al also showed in Al 2 O 3 / AlGaN/GaN structure that the C-V curves in the depletion region are stretched out more signicantly to the positive direction when the interface state density peaked at E C -0.1 eV is higher. 42 Signicant stretch out to the positive direction and high interface state density in the range of 0.1-0.2 eV observed for the sample with an AlN/Gd 2 O 3 bilayer, thus, can be associated with the nitrogen vacancy-related defects. Meanwhile, Freedsman et al showed in AlN/AlGaN/GaN MIS diodes that the trap density due to the AlN and AlGaN layers were located at 0.4-0.52 and 0.32-0.34 eV, respectively.…”
Section: Resultsmentioning
confidence: 89%